Digitalization Of The Industrial Revolution 4.0 Towards Improving Human Resource Management: Systematic Literature Review And Bibliometric Analysis - Nurfadilah, Ayu; Pratiwi, Dwi Dian; Pontoh, Grace T; Indrijawati, Aini (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2024)
This study provides an overview of the impact of Industry 4.0 digitalization on Human Resource Management (HRM) through a Systematic Literature Review. It highlights the paradigm shift induced by Industry 4.0, including the integration of technology in HRM, ethical challenges, and the role of humans in industrial digitalization. The findings indicate that industrial digitalization affects HRM and transforms organizational structures. The bibliometric analysis reveals a growing interest in this topic, with significant contributions from countries like Sweden, the United Kingdom, and Italy. The articles were published in various journal databases, with most ranked in Q1. The study concludes by emphasizing the importance of organizational adaptation to technological changes for success in a digitally connected era. This transformation presents challenges, such as changes in competency and skill demands, as well as opportunities for increased efficiency and productivity. Keywords: Digitalization, Industrial Revolution 4.0, Human Resource Management, Systematic Literature Review